Investigating the impact of aspartame on Alzheimer’s disease through network toxicology and molecular docking - Ge, Lili; Sun, Haitao; Zhang, Jianxin; Xu, Linlin; Ma, Lei; Jin, Zhi (Frontiers in Nutrition, 2026)
IntroductionAlzheimer’s disease (AD) is a prevalent neurodegenerative disorder, and the relationship between its pathogenesis and environmental factors has garnered increasing scholarly interest. Aspartame, a widely utilized artificial sweetener, has potential neurotoxic effects that remain incompletely understood. This study employs network toxicology and molecular docking to speculate on the potential molecular mechanisms by which aspartame is involved in the pathological process of AD.MethodsBy integrating data from multiple databases, including ChEMBL, SwissTargetPrediction, OMIM, and GeneCards, we obtained the shared targets of aspartame and AD. A protein–protein interaction (PPI) network was constructed using the STRING database and Cytoscape software to discern the core targets. Subsequently, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed via the DAVID database, and molecular docking validation of the core targets was conducted using AutoDock Vina.ResultsIn this study, a total of 298 targets associated with aspartame and 2,042 targets related to AD were identified. Seventy-five common targets were discovered, with BCL2, PPARG, TNF, IL1β, MAPK3, ESR1, and CASP3 were hypothesized as key core targets. GO functional analysis indicated that these targets are predominantly involved in biological processes such as protein metabolism, neuroinflammation, apoptosis, and oxidative stress. Furthermore, KEGG pathway analysis revealed significant enrichment in pathways TNF signaling, MAPK signaling, and PI3K-Akt signaling, among others. Molecular docking studies have shown that aspartame has A certain binding affinity with some core targets.DiscussionIt is speculated that aspartame may be involved in the key pathological processes of AD through multi-target and multi-pathway mechanisms, including neuroinflammation, apoptosis and amyloid-beta (Aβ) metabolism. This computational study speculates that aspartame, as an environmental exposure factor, is involved in the potential molecular mechanism of AD pathogenesis, thereby providing a theoretical basis for evaluating its neurotoxicity. Further experimental studies are needed in the future to confirm its biological effects.